NocturnOWL: Sleep-monitoring Virtual Pet Mobile Application - Kalaiselvan V.; Azman F.; Cheng L.K.; Rahim F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mobile computing; Biological clock; Cognitive development; Daily lives; Emotional attachments; Mobile app; Mobile applications; Sleep monitoring; Tracking mechanism; Sleep research